THE INTERPLAY OF IBD AND DEPRESSION IN INPATIENT LENGTH OF STAY, COST, AND COMPLICATIONS. (26th January 2023) - Dong, Rachel; Chang, Patrick; Zhang, Bing
Abstract: BACKGROUND: Many patients with inflammatory bowel disease (IBD) also have symptoms of depression. Both IBD and depression are associated with high healthcare utilization. In this cross-sectional study of population-based data, we sought to better characterize the impact of comorbid depression on hospitalizations of IBD patients. METHODS: We used the 2016-2018 National Inpatient Sample (NIS) from the United States Department of Health and Human Services to identify hospitalizations with IBD and depression using ICD-10 codes. ICD-10 codes also identified confirmed complications of IBD, such as rectal bleed, fistula, abscess, or intestinal obstruction. Hospitalizations for suicidal intent were excluded from our analysis. Health outcomes including length of stay (LOS), total cost, and complications of IBD were compared between IBD patients with and without depression. Patients with confirmed discharges were captured and survival curves were compared for time to discharge. Statistical analysis was performed using STATA, including two-sample t-testing and logistic regression (significance, p<0.01). RESULTS: Over three years, 129, 011 hospitalizations for IBD were isolated. Of these, 2, 124 hospitalizations (1.65%) were recognized to have both IBD and depression. Lengths of hospitalization for IBD patients with depression were longer than those without (mean LOS [95% CI]: 7.52 [7.06-7.98] vs. 5.28 [5.24-5.32], p<0.001) (Figure 1). Despite this, total cost of hospitalizations for IBD patients with depression was lower compared to IBD patients without depression ($mean [95% CI]: $47, 841 [43, 720-51, 963] vs. $53, 544 [53, 023-54, 065], p=0.008). Additionally, odds of hospitalization with IBD complication were lower in admissions coded for IBD with depression compared to without (OR [95% CI]: 0.52 [0.45, 0.61], p<0.001). On sub-analysis, hospitalizations of IBD patients with depression in partial or full remission had lower length of stay than hospitalizations of IBD with ongoing depression (mean LOS [95% CI]: 4.84 [3.90-5.79] vs. 7.52 [7.06-7.98], p<0.001) (Figure 2). CONCLUSIONS: While IBD patients with depression demonstrated lengthier hospitalizations compared to IBD patients without depression, the higher inpatient cost and complications from the latter group may reflect diagnostic, procedural, or surgical management of active disease. While major limitations of this administrative database include identification of hospitalizations instead of individual patients, as well as possibly underreporting or lower recognition of depression during hospitalization, our findings suggest that management of comorbid depression may reduce the length of stay in hospitalized patients with IBD.